Evaluation of On-Campus Practice Teaching at a Laboratory High School of a University using the Group-Level Assessment - Lapitan, May Ann B.; Angeles, Ann Jelin G.; Albor, Rufo Gil Z.; Bulasag, Abriel S.; Ancho, Inero V. (Journal of Social and Scientific Education, 2025)
The group-level assessment (GLA) is a type of participatory evaluation that involves stakeholders in generating themes and action plans in the process. The primary objective of this study is to evaluate the on-campus practice teaching program at a university laboratory high school (LHSU) using GLA. Since 2006, fourth-year students pursuing a Bachelor of Science in Mathematics and Science Teaching have participated in on-campus practice teaching at LHSU. The absence of systematic feedback collection and comprehensive evaluation has led to program supervision relying on anecdotal experiences and observations by LHSU coordinators and cooperating teachers (CTs). This study addresses this gap by aiming to identify strengths, needs, areas for improvement, and action plans generated by stakeholders. Employing a qualitative participatory design through GLA, 16 stakeholders participated, providing data through responses to open-ended prompts. Recognized strengths include the program’s role in translating theoretical knowledge into real-world teaching scenarios, while needs involve establishing on-campus teaching colloquia and a resource hub for teaching and learning materials. An identified area for improvement is enhancing feedback mechanisms. Stakeholders proposed action plans, including establishing partnerships with local and international teacher education institutions, and establishing a department for the mathematics and science teaching program. This study makes a substantial contribution by enhancing the quality of teacher preparation programs in mathematics and science education. Furthermore, this study serves as a valuable reference for future researchers engaged in the evaluation of practice teaching or education programs using GLA.